Oral leiomyoma: A case report on a rare lesion in oral cavity - Sharma, Pratibha S; Naikmasur, Venkatesh G; Nandimath, Kirty R; Burde, Krishna N; Hegde, Veda; Anehosur, Venkatesh (Journal of Oral Diagnosis, 2018)
Introduction: Leiomyoma, a benign tumour of smooth muscles, often affects uterine myometrium, GIT, skin and lower extremities of women of middle age group. Its occurrence in oral cavity is quite rare with reported incidence of 0.065%. It is contemplated that in oral cavity leiomyoma arise from smooth muscle wall of blood vessels chiefly affecting lips, tongue, palate, buccal mucosa, and rarely gingiva and mandible. Clinically the disease exhibits as a slow growing asymptomatic mass, occasionally associated with pain. Histopathological study is mandatory to help determine the diagnosis due to deceptive clinical appearance. Surgical excision is widely accepted as the best treatment modality with rare recurrence. Objective: The rationale of this case report is to help improve our understanding of this rare disease (oral leiomyoma) and to report its occurrence in the literature. Case Report: We report a rare case of a 25 years old female patient presenting with the chief complaint of a slow growing mass since 6 months, diagnosed as leiomyoma after clinical and histopathological examination. Conclusion: Leiomyoma is a benign tumour of smooth muscles with rare presentation in the oral cavity with good prognosis. Due to deceptive clinical and histopathological characteristics it is important to meticulously evaluate clinically and histopathologically to arrive at conclusive diagnosis.